Organic Semiconductors: Reversible Polymorphic Transition and Hysteresis‐Driven Phase Selectivity in Single‐Crystalline C8‐BTBT Rods (Small 3/2020). Issue 3 (23rd January 2020) - Kim, Min‐Woo; Kwon, Sooncheol; Kim, Jehan; Lee, Changhoon; Park, Ina; Shim, Ji Hoon; Jeong, Il‐Seok; Jo, Yong‐Ryun; Park, Byoungwook; Lee, Joo‐Hyung; Lee, Kwanghee; Kim, Bong‐Joong
Abstract : In article number 1906109, Kwanghee Lee, Bong‐Joong Kim, and co‐workers synthesize a polymorph of a single crystalline 2, 7‐dioctyl[1] benzothieno[3, 2‐b][1]benzothio‐phene (C8‐BTBT) rod on a low molecular weight poly(methyl methacrylate) (PMMA), which exhibits a reversible change in resistivity by 5.5 orders with hysteresis during thermal cycling. Varying cycling temperatures leads to diverse resistivities near room temperature, important for non‐volatile multivalue memories. The polymorph transforms as molecules tilt, thus only a homogeneous single‐crystalline phase appears at each temperature.